Al-qarinah (circumstantial Evidence) And Its Capacity In Criminal Cases, Munakahat And Wealth Convictions According To Islam - Lukman Abdul Mutalib; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Abd Hamid Abd Murad; Kamarul Arifin Mohd Wafa; Mohd Faisal Mohamed,; Asmawati Suhid (Science and Engineering Research Support Society, 2024)
Indexed by Scopus/ERA